2011
DOI: 10.1039/c1cp20404a
|View full text |Cite
|
Sign up to set email alerts
|

The CH/π hydrogen bond in chemistry. Conformation, supramolecules, optical resolution and interactions involving carbohydrates

Abstract: The CH/π hydrogen bond is an attractive molecular force occurring between a soft acid and a soft base. Contribution from the dispersion energy is important in typical cases where aliphatic or aromatic CH groups are involved. Coulombic energy is of minor importance as compared to the other weak hydrogen bonds. The hydrogen bond nature of this force, however, has been confirmed by AIM analyses. The dual characteristic of the CH/π hydrogen bond is the basis for ubiquitous existence of this force in various fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
455
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 804 publications
(494 citation statements)
references
References 334 publications
(164 reference statements)
34
455
0
5
Order By: Relevance
“…This type of interaction is also present between the isopropylamine side chain of propranolol and the residue Trp104 in the medium pocket of CalB, involving the six-membered ring of this residue, in agreement with its higher propensity to form CH-π interactions compared with the five-member ring [4]. As the strength of a CH-π interaction depends on its distance and directionality (the stronger the interaction, the stronger the trend to linearity) [5], the stabilization of each TI-2 in binding mode I is expected to depend strongly on the orientation of the side chains of propranolol in the binding pocket, especially that of its naphthyl group due to its bulky size and its π-donor character. Therefore these CH-π interactions are expected to play an important role in the stabilization of the corresponding transition states (TSs) and thus in the enantioselectivity of the reaction.…”
Section: Analysis Of the Ti-2 Structures Of R-and S-propranolol In Bisupporting
confidence: 53%
“…This type of interaction is also present between the isopropylamine side chain of propranolol and the residue Trp104 in the medium pocket of CalB, involving the six-membered ring of this residue, in agreement with its higher propensity to form CH-π interactions compared with the five-member ring [4]. As the strength of a CH-π interaction depends on its distance and directionality (the stronger the interaction, the stronger the trend to linearity) [5], the stabilization of each TI-2 in binding mode I is expected to depend strongly on the orientation of the side chains of propranolol in the binding pocket, especially that of its naphthyl group due to its bulky size and its π-donor character. Therefore these CH-π interactions are expected to play an important role in the stabilization of the corresponding transition states (TSs) and thus in the enantioselectivity of the reaction.…”
Section: Analysis Of the Ti-2 Structures Of R-and S-propranolol In Bisupporting
confidence: 53%
“…87 Additionally, a particular class of interaction, usually classified as a weak H-bond and a type of π interaction, is the CH-π interaction. 88,89,90 It consists of the interaction between a CH bond and a orbital belonging to an aromatic molecule. This interaction exhibits some directional character, which favors linear self-assembled structures.…”
Section: Hydrogen Bondingmentioning
confidence: 99%
“…The weakest H-bonding interactions are established between weakly polarized D-H bonds (e.g., aliphatic CH) and mildly electron-rich H-acceptor moieties (e.g., alkene π-electrons) [21][22][23]. While a single interaction is energetically insignificant, when several weak H-bonds coexist they can stabilize protein structures [24][25][26] and contribute to the binding of proteins to carbohydrates [27][28][29][30][31]. Apart from this weak bonding interaction, recent theoretical explorations have suggested that pnicogen and tetrel atoms in their sp 3 hybridized form can act as electron poor entities suitable to accommodate an electron-rich guest [16,[32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%